Acute and Late Toxicity after Three-Dimensional Conformal Image-Guided Radiotherapy for Localized Prostate Cancer. (26th December 2014) - Ingrosso, Gianluca; Carosi, Alessandra; Ponti, Elisabetta; Murgia, Alessandra; di Cristino, Daniela; Barbarino, Rosaria; Benassi, Michaela; Di Murro, Luana; Giudice, Emilia; Bove, Pierluigi; Santoni, Riccardo
<x xml:space="preserve">Abstract</x> We evaluated the clinical impact of a high definition micro-multileaf collimator and a linac-integrated cone-beam computed tomography in 142 patients treated with conformal radiotherapy for localized prostate cancer to a total dose of 76 Gy. Details on treatment toxicity and tumour control were collected. The 3 years biochemical relapse-free survival was 90%. Acute and late gastrointestinal toxicities were low (3-year actuarial late toxicity of 11.2%). Acute genitourinary toxicity was relatively high, the 3-year actuarial genitourinary late toxicity was 12%. Conformal image-guided radiotherapy for localized prostate cancer leads to low rates of late toxicity with a high rate of tumor control.